2023
DOI: 10.1039/d3cp00366c
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ohmic nanoconductors: myth, reality and promise

Abstract: The recent accomplishment in the design of molecular nanowires characterized by an increasing conductance with length have embarked the origin of extraordinary new family of molecular junctions referred to as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…This suggests that both the PBE and HSE06 functionals result in similar electronic structures of ZGNRs, except that HSE06 shows a larger bandgap. We have studied the effect of hybrid functionals on the transport properties of molecular systems in our previous work [48]. Hybrid functionals can provide quantitative estimates of conductance, while the GGA functional can provide a qualitative understanding of the transport properties of the system.…”
Section: Spin Symmetry In Zgnrsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that both the PBE and HSE06 functionals result in similar electronic structures of ZGNRs, except that HSE06 shows a larger bandgap. We have studied the effect of hybrid functionals on the transport properties of molecular systems in our previous work [48]. Hybrid functionals can provide quantitative estimates of conductance, while the GGA functional can provide a qualitative understanding of the transport properties of the system.…”
Section: Spin Symmetry In Zgnrsmentioning
confidence: 99%
“…Various schemes have been proposed to modulate ZGNR's magnetic properties for different device applications, such as chemical functionalizations and substitutions, and the exploitation of quantum interference (QI) effects to control spinpolarized electron transmission [45][46][47][48][49][50][51][52][53][54]. Saraiva-Souza et al reported the observation of destructive quantum interference (DQI) features in the electron transmission spectrum by adding an imidazole donor group to the polyacetylene chain connected to the ZGNR electrodes [55].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this challenge, growing efforts have aimed at engineering the molecule’s electronic structure to enhance the molecular conductance while battling against the length-dependent decay. Ideally, reaching the reverse conductance/length trend, known as antiohmic behavior, in single molecular wires is long thought-after for the development of novel quantum electronic technology, energy harvesting, and photosynthesis applications. In addition, long-range charge transport in molecules will play a crucial role in future nanodevices where CMOS-compatible molecules with outstanding performance and scalability are integrated.…”
Section: Introductionmentioning
confidence: 99%